PENGEMBANGAN TPA DARUS SALAM MELALUI PENAMBAHAN MADRASAH DINIYAH DI DUSUN PENTUNG MANGIR DESA KALIPEPE LUMAJANG - Afida, Ifa; Permatasari, Yovita Dyah; Marwiyah, Syarifatul; Uke, Ora Gorez; Atho'illah, Atho'illah; Rohman, Oky Abdul; Maulida, Jilan; Agustiningsih, Reni (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
This research-based community service aims to foster and develop Islamic religious education so that students better understand the Islamic context quickly and pleasantly. Teaching and learning activities in a comfortable situation make students more enthusiastic about acquiring knowledge. Madrasah Diniyah is one level higher than TPA in religious education. The problem in the field is that there are no Diniyyah madrasahs within the Darus Salam TPA. Students, after graduating from TPA, recite the Koran as usual. The method used in this service activity is the learning method, which involves rote memorization, discussion, and practicum. This research-based service becomes more interesting by implementing character education for students. The results of this research-based community service show significant changes, namely, students can continue to acquire knowledge at the Diniyyah level and receive character education training in every learning process.